The Effect of the Mind Mapping Method on the Narrative Writing Ability of Class V Students of School: Pengaruh Metode Mind Mapping (Peta Pikiran) Terhadap Kemampuan Menulis Narasi Siswa Kelas V di Sekolah - Yanuari Ingsih; Choirun Nisak Aulina (Academia Open, 2022)
The influence of the Mind Mapping Method on the narrative writing skills of the fifth grade students of MI Ma'arif Sentul. Thesis of Elementary School Teacher Education Study Program, Faculty of Psychology and Educational Sciences, Muhammadiyah University of Sidoarjo. This study aims to describe the effect of the mind mapping method on the ability to write narratives for fifth grade students at MI Ma'arif Sentul. This research uses quantitative research. The method used is pre-experimental design with One Group Pretest-Posttest research design. The instruments in this research consist of learning instruments in the form of syllabus, lesson plans, teaching materials, worksheets for class V MI Ma'arif Sentul students using saturated samples. Data collection in this study used tests, namely pretest and posttest on writing skills. This study determines the data analysis technique using descriptive analysis techniques and analysis in the form of normality tests and hypothesis testing, the results of the study show that the mind mapping method has an influence on writing skills.